Pengaruh Sertifikat Halal, Kualitas Produk dan Strategi Pemasaran Terhadap Penjualan Produk Makanan Home Industry - Sania Rizki Maharani; Cupian Cupian; Adhi Prapaskah Hartadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study focuses on examining the impact of halal certification, product quality, and marketing strategy on the sales of Home Industry food products. A descriptive quantitative approach was adopted to analyze the relationship between variables. Data were collected through questionnaires distributed to 170 respondents who were food product business actors Home Industry in Sariwangi District, Tasikmalaya Regency, West Java Province. The collected data were analyzed using the Structural Equation Modeling method with a Partial Least Squares (PLS-SEM) approach. The results show that both halal certification and marketing strategy have a significant positive effect on sales of Home Industry food products. Meanwhile, product quality does not show a significant effect on sales. The study also indicates that halal certification has the strongest influence on sales compared to the other variables.